Knowledge, Skills, and Appreciation in Oil Painting among Students in Vocational Colleges in China: An Opportunity for Professional Development Training - Wang, Qiangui; Layla P.Padolina (International Journal of Social Sciences and Public Administration, 2024)
This study investigates students' knowledge, skills and appreciation level in oil painting in Chinese vocational colleges and universities. It explores the influencing factors and current situation of oil painting among students in Chinese vocational colleges. In addition, based on the investigation and analysis, opportunities to enhance students' professional development training are proposed. This paper collects, organizes and analyzes data related to oil painting of students in vocational colleges and universities in China by means of questionnaire analysis of 303 students, and the results of the study show that students have different levels of interest and motivation in oil painting. Professional development training is needed to improve their knowledge, skills and appreciation of oil painting. Such training can enhance their practical skills and develop creative thinking and aesthetic vision. The significance of this study suggests that strengthening oil painting education in vocational colleges and universities is crucial for students' personal growth and professional development. It also has a positive impact on promoting art education in China. Recommendations include providing more diverse teaching resources and methods, as well as increasing practice opportunities.